Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1038/bjc.2011.432
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TMPRSS4 in non-small cell lung cancer is associated with poor prognosis in patients with squamous histology

Abstract: Background:Mortality rates in lung cancer patients have not decreased significantly in recent years, even with the implementation of new therapeutic regimens. One of the main problems is that a large proportion of patients present local or distant metastasis at the time of diagnosis. The need for identification of novel biomarkers and therapeutic targets for a more effective management of lung cancer led us to investigate TMPRSS4, a protease reported to promote tumour growth and metastasis.Material and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 23 publications
(50 reference statements)
5
69
0
Order By: Relevance
“…In breast cancer, higher expression of TMPRSS4 was associated with positive lymph node metastasis, larger tumor size, advanced pathological grade, and shorter overall and disease-free survival; 16 in non-small cell lung cancer, overexpression of TMPRSS4 in patients with squamous histology was associated with poor prognosis; 24 in malignant thyroid neoplasm, TMPRSS4 was identified to be a diagnostic marker. 25 Of note, Jung et al had reported TMPRSS4 was upregulated in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, higher expression of TMPRSS4 was associated with positive lymph node metastasis, larger tumor size, advanced pathological grade, and shorter overall and disease-free survival; 16 in non-small cell lung cancer, overexpression of TMPRSS4 in patients with squamous histology was associated with poor prognosis; 24 in malignant thyroid neoplasm, TMPRSS4 was identified to be a diagnostic marker. 25 Of note, Jung et al had reported TMPRSS4 was upregulated in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we showed that increased TMPRSS4 mRNA levels were associated with poor prognosis in SCC patients [7]. TMPRSS4 has also been found upregulated in colon, pancreas, breast, cervix, thyroid and liver tumors [8, 9, 10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequebt data show that TMPRSS4 induces invasion and epithelial-mesenchymal transition through upregulation of integrin alpha5 and its signaling pathways [15]. Recent studies indicate that overexpression of TMPRSS4 is significantly associated with reduced overall survival of patients with non-small cell lung cancer and breast cancer and may represent a potential therapeutic target [10][11]16]. However, to date, there is no report to clarify the prognostic impact of TMPRSS4 expression in GC.…”
Section: Discussionmentioning
confidence: 96%